Nanoformulations Enabled Possible Solutions for the Management of Psoriasis - Gupta, Rishabh; Srivastava, Nimisha (Current Cosmetic Science, 2022)
Psoriasis is a chronic inflammatory disease with clinical skin manifestations that affect adults and children. It can significantly negatively impact the physical, emotional, and psychosocial well-being of affected patients. It has a strong genetic component, but environmental factors such as infections can play an important role in the presentation of the disease. Patients suffering from a severe phase of this disease may have greater chances of other diseases like cardiovascular diseases, non-melanoma, and lymphoma. The present review majorly focuses on the hallmarks of different types of psoriasis, the evaluation of biomarkers to establish the severity and therapeutic response, and novel targeted therapies for managing psoriasis. Potential herbal extracts and bioactive for treating psoriasis are also highlighted here. A summary of pertinent, peer-reviewed English literature from databases like EBM, EMBASE and MEDLINE from 2010 to 2021 is used.
Keywords: targeted therapy